2003
DOI: 10.1016/s0378-8741(02)00146-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of ethanol and water extracts of Cassia alata

Abstract: Crude ethanol and water extract of leaves and barks from Cassia alata were tested in vitro against fungi, (Aspergillus fumigatus and Microsporum canis), yeast (Candida albicans) and bacteria (Staphylococcus aereus and Escherichia coli). C. albicans showed concentration-dependent susceptibility towards both the ethanol and water extracts from the barks, but resistant towards the extracts of leaves. The degree of susceptibility varied, the water extract from barks showed bigger inhibition zone than the ethanol e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(97 citation statements)
references
References 5 publications
5
82
0
10
Order By: Relevance
“…Other researchers have also assessed the antibacterial efficacy of ethanolic extract of A. indica. 25,26 Assessment has also been performed on the prophylactic activities of A. indica with several extracts such as methanol, acetone, chloroform, petroleum ether, and n-hexane. 27 Findings in this previous study were similar to those in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have also assessed the antibacterial efficacy of ethanolic extract of A. indica. 25,26 Assessment has also been performed on the prophylactic activities of A. indica with several extracts such as methanol, acetone, chloroform, petroleum ether, and n-hexane. 27 Findings in this previous study were similar to those in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Viana et al (2008) enfatizam que atividade antifúngica de extratos de plantas pode estar influenciada pelo ambiente ao qual a planta foi submetida, a fatores genéticos, a utilização de diferentes métodos de extração, ao pH, a temperatura e ao uso de diferentes concentrações. Vários trabalhos mostram que o uso de diferentes concentrações pode interferir nos resultados obtidos em experimentos onde foram utilizadas as mesmas espécies vegetais (Ranganathan & Balajee, 2000;Somchit et al, 2003).…”
Section: Diâmetro Das Colôniasunclassified
“…A dermatofitose é, comparativamente, uma condição clínica comum tanto em animais de companhia como em animais de criação (Tortora et al, 2002;Hirsh & Zee, 2003;Quin et al, 2005). As dermatofitoses podem ser transmitidas de animal para animal, de animal para seres humanos, ou do solo para os animais e para os seres humanos (Minami, 2003).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In Suriname, root extracts from C. alata are used for the treatment of uterus disorders [1]. Pharmacological investigations performed so far on C. alata have shown that this herb has several biological activities, such as antimicrobial [8,9], antifungal [2,10,11], purgative [4], anti-inflammatory [11,12], analgesic [1,11,13], antitumor [14], and hypoglycaemic [11] activities.…”
Section: Published In Final Edited Form Asmentioning
confidence: 99%